Developmental plasticity and stability in the tracheal networks supplying Drosophila flight muscle in response to rearing oxygen level. (April 2018) - Harrison, Jon F.; Waters, James S.; Biddulph, Taylor A.; Kovacevic, Aleksandra; Klok, C. Jaco; Socha, John J.
Graphical abstract: Highlights: Larger individuals had larger flight muscles and macro-tracheal supply. Drosophila did not enlarge macro-tracheal supply to the flight muscles when reared at lower oxygen. Tracheolar density showed strong compensatory responses to rearing oxygen level. Axial diffusing capacity decreased with successive branching of the tracheoles. Abstract: While it is clear that the insect tracheal system can respond in a compensatory manner to both hypoxia and hyperoxia, there is substantial variation in how different parts of the system respond. However, the response of tracheal structures, from the tracheoles to the largest tracheal trunks, have not been studied within one species. In this study, we examined the effect of larval/pupal rearing in hypoxia, normoxia, and hyperoxia (10, 21 or 40 kPa oxygen) on body size and the tracheal supply to the flight muscles of Drosophila melanogaster, using synchrotron radiation micro-computed tomography (SR-µCT) to assess flight muscle volumes and the major tracheal trunks, and confocal microscopy to assess the tracheoles. Hypoxic rearing decreased thorax length whereas hyperoxic-rearing decreased flight muscle volumes, suggestive of negative effects of both extremes. Tomography at the broad organismal scale revealed no evidence for enlargement of the major tracheae in response to lower rearing oxygen levels, although tracheal size scaled with muscle volume. However, using confocal imaging, we found a strong inverse relationship between tracheole density within the flight muscles and rearing oxygen level, and shorter tracheolar branch lengths in hypoxic-reared animals. Although prior studies of larger tracheae in other insects indicate that axial diffusing capacity should be constant with sequential generations of branching, this pattern was not found in the fine tracheolar networks, perhaps due to the increasing importance of radial diffusion in this regime. Overall, D. melanogaster responded to rearing oxygen level with compensatory morphological changes in the small tracheae and tracheoles, but retained stability in most of the other structural components of the tracheal supply to the flight muscles.